Knowledge and practice on muscle cramps and their influencing factors among the school cricketers in Jaffna Educational Zone - Abeysinghe, A.H.M.C.I.; Abayasinghe, B.T.S.; Thabotharan, D.; Sabaananth, S. (University of Jaffna, 2024)
Introduction: Cricketers often face muscle cramps, leading to considerable pain during games. School cricketers, with limited knowledge and practice, are particularly at risk; therefore, evaluating their knowledge and practice on muscle cramps is essential to prevent muscle cramps during competitions. Objective: To assess the knowledge and practice on muscle cramps and their influencing factors among the school cricketers in Jaffna Educational Zone. Methodology: A descriptive cross-sectional study was done among 382 school cricketers who played for the school teams of Jaffna Educational Zone. Ethical approval was obtained from the Ethics Review Committee, Faculty of Medicine, University of Jaffna, and the participation was selected after getting informed consent. A pre-designed and validated self-administered questionnaire was used to assess the participants' knowledge and practices related to muscle cramps over one month. The data was analysed by using SPSS 27 and a Chi-Squared test was performed to identify the influencing factors. Results: The mean age of the participants was 16 (SD=2.244). All the respondents were male and played under 19 cricket teams. Among the participants, 87% had good knowledge of muscle cramps while. 61.3% had good practice. Furthermore, 45% of participants experienced muscle cramps in their cricketing career. A statistical significance association (p=0.027) was found between muscle cramps and warm-down or cooling exercises. However, stretching exercises, conditioning exercises and recovery sessions were not statistically significant with muscle cramps occurring in cricketers. Conclusion: The knowledge and practice of muscle cramps among school cricketers in the Jaffna educational zone are 87% and 61.3%, respectively. It is recommended to do an awareness program among school crickets to further improve their knowledge and practices on muscle cramps to prevent them from muscle injuries.
Keywords: Muscle cramps; School cricketers; Knowledge; Practice; Jaffna Educational Zone